2017
DOI: 10.1038/bjc.2017.145
|View full text |Cite
|
Sign up to set email alerts
|

A phase Ib study of pembrolizumab plus chemotherapy in patients with advanced cancer (PembroPlus)

Abstract: Background:Pembrolizumab (P) is an anti-PD-1 antibody that blocks the interaction between programmed cell death protein 1 (PD-1) on T-cells and PD-L1 and PD-L2 on tumour cells. A phase Ib trial of P plus chemotherapy was undertaken to evaluate the safety and efficacy.Methods:Patients with advanced, metastatic solid tumours were enrolled onto one of six treatment arms. Pembrolizumab was given: with gemcitabine (G), G+docetaxel (D), G+nab-paclitaxel (NP), G+vinorelbine (V) or irinotecan (I) until progression or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
84
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(85 citation statements)
references
References 21 publications
(24 reference statements)
1
84
0
Order By: Relevance
“…Aiming at improving the anticancer effect, many other treatment methods have been combined with immunotherapy in pre‐clinical studies or even in clinical trials recently . Chief among them, chemotherapy is regarded as a proper candidate for such combination therapy owing to its effective tumor growth inhibition .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aiming at improving the anticancer effect, many other treatment methods have been combined with immunotherapy in pre‐clinical studies or even in clinical trials recently . Chief among them, chemotherapy is regarded as a proper candidate for such combination therapy owing to its effective tumor growth inhibition .…”
Section: Introductionmentioning
confidence: 99%
“…Aiming at improving the anticancer effect, many other treatment methods have been combined with immunotherapy in pre‐clinical studies or even in clinical trials recently . Chief among them, chemotherapy is regarded as a proper candidate for such combination therapy owing to its effective tumor growth inhibition . More critically, increasing evidences are showing that some chemotherapeutic agents such as anthracyclines and taxanes not only induce the apoptosis of tumor cells, but also cause immunogenic cell death (ICD) to activate immune system .…”
Section: Introductionmentioning
confidence: 99%
“…PembroPlus trial (NCT02331251) is a phase 1b-2 study that evaluated the role of pembrolizumab in combination with different cytotoxic agents (16 In conclusion, despite the promising signal of efficacy of pembrolizumab in advanced ED-SCLC disease, as highlighted in this small size clinical trial, there is an urgent need for a better understanding. First, finding a better predictive biomarker for a more accurate identification of patients most likely to benefit from anti-PD1 inhibition is of crucial relevance.…”
Section: S81mentioning
confidence: 97%
“…In total 11 patients with metastatic PDAC (after first-line chemotherapy or treatment naïve) received chemotherapy in combination with pembrolizumab. Two patients showed a partial remission, 6 patients had a stable disease [25]. Interim results from a phase I trial combining nivolumab plus nab-paclitaxel with or without gemcitabine showed a response in 12 out of 17 patients (5 patients partial remission, 7 patients stable disease) with locally advanced or metastatic PDAC [26].…”
Section: The Pd-1/pd-l1 Pathwaymentioning
confidence: 99%